Tell me about this, Bawoo! edutainment for the curious Filipino-Korean child designing a social media campaign that explores character design to encourage Filipino-Korean damunhwa children aged 9 to 12 to interact with Philippine culture - Youn, Gabrielle Natividad A.; Austria, Romanlito S. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2023)
Filipino-Korean damunhwa, or multicultural, children who are born in South Korea grow up surrounded by their Korean communities, and thus strongly identify with Korean culture. However, due to the limitations of the current damunhwa education in Korea, Filipino-Korean children have limited opportunities to learn about their Philippine heritage. Moreover, analysis of South Korean media shows that the image of the Philippines in South Korean media has not been positive. This could be detrimental, as Filipino-Korean children already lack exposure to Philippine culture. Currently, damunhwa education in South Korea focuses on integrating damunhwa people into Korean society, and lacks effort in encouraging the formation of a collective identity among damunhwa children.

Studies highlighted in this research show that social media and edutainment can encourage children to form positive reactions to the content they are consuming. Since South Korea has the advantage of widespread internet connectivity as well as smartphone accessibility, social media can be utilized as an educational tool in damunhwa education. Additionally, South Korea has a developed character industry that all age groups actively consume. This research will explore the use of a character design in a social media campaign.

The goal of this study is to create a model of social media campaign edutainment with a character design that can encourage Filipino-Korean children to interact with Philippine culture to form a collective identity.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 110-112
Keywords: Damunhwa; Collective identity; Learn through play